Random walk as a universal test of weak-form foreign exchange market efficiency : a theoretical proof - Ghartey, Edward E. ([CCMS] [St. Augustine]TT, 2001)
Seeks to show that the pure random walk spot exchange rate is an adequate means to universally test foreign exchange market efficiency.